2018
DOI: 10.1161/jaha.118.010690
|View full text |Cite
|
Sign up to set email alerts
|

Role of ADTRP (Androgen‐Dependent Tissue Factor Pathway Inhibitor Regulating Protein) in Vascular Development and Function

Abstract: Background The physiological function of ADTRP (androgen‐dependent tissue factor pathway inhibitor regulating protein) is unknown. We previously identified ADTRP as coregulating with and supporting the anticoagulant activity of tissue factor pathway inhibitor in endothelial cells in vitro. Here, we studied the role of ADTRP in vivo, specifically related to vascular development, stability, and function. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
30
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(31 citation statements)
references
References 70 publications
0
30
1
Order By: Relevance
“…S2F). This finding contrasts with a recent report that described an independently-generated ADTRP-deficient mouse strain that exhibited moderately decreased viability and non-Mendelian offspring ratios (21). We suspect that differences between our knockout strategy, which removed 13-bases from the locus, and that of the reported approach, which deleted approximately 38 kb of the genomic region between exons 3 and 5, might underlie the variance.…”
Section: Discussioncontrasting
confidence: 93%
See 1 more Smart Citation
“…S2F). This finding contrasts with a recent report that described an independently-generated ADTRP-deficient mouse strain that exhibited moderately decreased viability and non-Mendelian offspring ratios (21). We suspect that differences between our knockout strategy, which removed 13-bases from the locus, and that of the reported approach, which deleted approximately 38 kb of the genomic region between exons 3 and 5, might underlie the variance.…”
Section: Discussioncontrasting
confidence: 93%
“…Depletion of ADTRP in endothelial cells reduced TFPI levels, an observation that was attributed to the ability of these two proteins to interact in the plasma membrane (19). More recently, deletion of ADTRP in mice was reported to cause vascular dysfunction, though the mechanism by which this occurs is unclear (21). AIG1 is homologous to ADTRP and was discovered in human dermal papilla cells as an androgen-regulated gene (22).…”
Section: Introductionmentioning
confidence: 99%
“…Figure 3 illustrates examples of ADTRP localization in mouse tissues. The mRNA expression of Adtrp increased significantly (3–4 times) during embryogenesis [ 39 ]. Another group also reported localization of mouse ADTRP in the liver, adipose tissue, kidney, and duodenum [ 40 ].…”
Section: Structure Expression and Tissue Localization Of Adtrpmentioning
confidence: 99%
“…In zebrafish, we showed by in-situ hybridization that adtrp is expressed in the lateral plate mesoderm, most likely in angioblasts, and in both the dorsal aorta and cardinal vein [ 39 ]. qPCR revealed that the mRNA expression of adtrp increased up to 50 times during zebrafish embryonic development and into adulthood [ 39 ].…”
Section: Structure Expression and Tissue Localization Of Adtrpmentioning
confidence: 99%
See 1 more Smart Citation